1994
DOI: 10.1002/1097-0142(19941001)74:7+<2118::aid-cncr2820741720>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact of cancer on older versus younger patients and their families

Abstract: Past studies of the psychosocial aspects of cancer have been largely descriptive, with little discussion of differences among cancer patients. Age differences have been noted repeatedly in studies of the effects of various cancer treatments. To determine whether age differences are also present the prevalence of various psychosocial problems often associated with cancer, analyses of data obtained from several different studies of Rhode Island cancer patients' psychosocial conditions were conducted, comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
155
6
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(184 citation statements)
references
References 25 publications
17
155
6
3
Order By: Relevance
“…Previous studies have suggested that age is related positively to emotional functioning (Vinokur et al, 1990;Ganz et al, 1992;Moor et al, 1994). In this sample, older individuals did not have better scores on the subscale psychological well-being, as measured by the QOL-CA scale, than younger patients.…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…Previous studies have suggested that age is related positively to emotional functioning (Vinokur et al, 1990;Ganz et al, 1992;Moor et al, 1994). In this sample, older individuals did not have better scores on the subscale psychological well-being, as measured by the QOL-CA scale, than younger patients.…”
Section: Resultscontrasting
confidence: 51%
“…In contrast, Vinokur et al (1990) identified age in women with breast cancer (Lauria, 1991). Improved emotional responses and fewer rehabilitation problems were found in older rather than in younger cancer patients (Vinokur et al, 1990;Ganz et al, 1992;Moor et al, 1994).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This pattern has been observed in a study investigating psychosocial concerns (Harrison and Maguire, 1995) and one looking into unmet need (Mor et al, 1994). Younger people may have to cope with demands from a wide range of life domains including employment and child care which are less likely to be of significance to the older age groups.…”
Section: Social Problems In Oncology Ep Wright Et Almentioning
confidence: 77%
“…Sociodemographic characteristics include variables like age, gender, living situation, type of relationship, and socioeconomic status of both the care recipient and caregiver. Relatively consistent findings were reported regarding gender (Zarit and Toseland, 1986;Barusch and Spaid, 1989;Miller and Cafasso, 1992), age (Mor et al, 1994), co-residence and the type of relationship between the care recipient and caregiver (Horowitz, 1985;George and Gwyther, 1986;Young and Kahana, 1989).Women, especially those at a younger age, tend to perceive caregiving as more negative than (older) men and report higher levels of psychological distress (Zarit et al, 1989;Blood et al, 1994), even if the amount of care provided and/or the level of patient's health is controlled (Horowitz, 1985). Compared to other informal caregivers, female caregivers and partners are identified as the most vulnerable group of caregivers.…”
Section: Contextual Factors In the Caregiving Processmentioning
confidence: 99%